In vitro and in vivo safety evaluation of Dipteryx alata Vogel extract - Esteves-Pedro, Natalia Mencacci; Borim, Thaisa; Nazato, Virginia Sbrugnera; Silva, Magali Glauzer; Lopes, Patricia Santos; dos Santos, Marcio Galdino; Dal Belo, Chariston Andre; Primila Cardoso, Cassia Regina [UNESP]; Varanda, Eliana Aparecida [UNESP]; Groppo, Francisco Carlos; Gerenutti, Marli; Oshima-Franco, Yoko (Biomed Central Ltd., 2012)
Background: Dipteryx alata Vogel popularly known as baru is an important commercial leguminous tree species from the Brazilian Cerrado, which possess medicinal properties, besides its fruits consumption by animals and humans. The use of the naturally occurring plants as herbal remedies and foods mainly from leaves, seeds, flowers and roots of plants or extracts require precautions before ensuring these are safe and efficacious. The objective of this study was to evaluate the safety of D. alata barks extract.Methods: Vegetal drugs of D. alata barks were submitted to quality control assays and further to the safety assays under 1) in vitro parameter by Salmonella (Ames) mutagenicity, and 2) in vivo parameter on the pregnancy of rats.Results: The extract was non-mutagenic to any of the assessed strains TA97a, TA98, TA100 and TA102 even after metabolic activation (+S9). All in vivo parameters (reproductive ability evaluation, physical development of rat offsprings, and neurobehavioral development assays) showed no changes related to control group.Conclusion: D. alata barks extract is neither mutagenic by the Ames test nor toxic in the pregnancy of rats, with no physical-neurobehavioral consequences on the rat offsprings development.